Effects of Exchanging Battery on the Electric Vehicle’s Electricity Consumption in a Single-Lane Traffic System - Shi-Chun Yang; Wen-Zhuang Gou; Tie-Qiao Tang; Hua-Yan Shang (Journal of Applied Mathematics)
We propose a car-following model to explore the influences of exchanging battery on each vehicle’s electricity consumption under three traffic situations from the numerical perspective. The numerical results show that exchanging battery will destroy the stability of traffic flow, but the effects are related to each vehicle’s initial headway, the time that each electric vehicle exchanges the battery, the proportion of the electric vehicles that should exchange the battery, the number of charging stations, and the distance between two adjacent charging stations.